Pengaruh Brand Ambassador, E-Service terhadap Keputusan Pembelian melalui Minat Beli di Tokopedia - Selly Merlina Moko; Rivera Pantro Sukma (Panorama Nusantara, 2023)
This study aims to determine the effect of Brand ambassador, E-service on purchasing decisions through Buying interest on Tokopedia. The population in this study were Tokopedia consumers. The sampling technique used was accidental sampling with a sample size of 200 respondents. The data collection method uses a questionnaire distributed to respondents and has been tested for validity and reliability. The results showed that brand ambassador has a positive and significant effect on purchasing decisions, brand ambassador has a positive and significant effect on buying interest, e-service has a positive and significant effect on purchasing decisions, e-service has a positive and significant effect on buying interest, buying interest has a positive and significant effect on purchasing decisions, brand ambassador has an indirect effect on purchasing decisions through buying interest and e-service has an indirect effect on purchasing decisions through Buying interest. The coefficient of determination on buying interest is 58.4% and purchase decision is 81.6%.